Asia-Pacific Fishing Livelihoods - Fabinyi, Michael; Barclay, Kate (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"Where fishing livelihoods come from and where they are going are simple questions with no simple answers. Using examples of small-scale fisheries in Asia-Pacific, Fabinyi and Barclay offer eloquent analyses of how fishing livelihoods are shaped, resting on a relational approach idea. The book is a must-read for policy makers and practitioners looking for rare insights in the social sciences of fisheries, to broaden their governance solutions". -Ratana Chuenpagdee, Memorial University of Newfoundland, Canada "In this book, Fabinyi and Barclay draw on their extensive research to take us across Asia and the Pacific to show the ways in which fishing livelihoods are entangled with coasts, lakes, rivers, agricultural and urban spaces. Their account challenges us to think beyond the now - to past and future regimes and social-ecological configurations. They provoke us to engage with the power-laden processes and structures that enable and constrainchange to fishing livelihoods as we know them now". -Philippa Cohen, Resilient Small-Scale Fisheries Program Leader, WorldFish "It is not just about the fish! Armed with pragmatism and case studies, Fabinyi and Barclay help us see fishing livelihoods through diverse and dynamic social, economic and political lenses". -Sangeeta Mangubhai, Director, Fiji Country Program, Wildlife Conservation Society This open access book explores fishing livelihoods within their wider contexts. Drawing on case studies from across the Asia-Pacific region, the book highlights how fishing livelihoods are shaped by globalisation, social relationships and governance. The book concludes by showing how better understanding these relationships can contribute to governance for healthier ecosystems and social wellbeing. Michael Fabinyi is an Associate Professor in the Faculty of Arts and Social Sciences at the University of Technology Sydney (UTS). His research interests are focused on the social and political aspects of marine resource management and use, including coastal livelihoods, fisheries governance and fisheries trade. Kate Barclay is a Professor in the Faculty of Arts and Social Sciences at UTS. Her research interests are the governance of marine areas and resources, including social and economic aspects of seafood value chains, social inclusion in fisheries, and the wellbeing of people in coastal communities.